Antimicrobial activity study of ethanolic extract of Alternanthera sessilis linn. aerial parts - D., Ashok Kumar; Das, Mrinmay; Mohanraj, P.; Das, Arup (Creative Pharma Assent, 2014)
The ethanolic extract of Alternanthera sessilis Linn. was evaluated for antimicrobial activity study against medically important gram-positive bacteria such as Staphylococcus aureus, Bacillus subtilis, Bacillus polymexia & Streotococcus faecalis, gram negative bacteria such as Pseudomonas aerugenosa, Salmonella typhii, Shigella dysenteriae & Escherichia coli and fungi like Penicillum notatum, Aspergillus niger & Candida albicans. The in-vitro antimicrobial activity, minimum inhibitory concentration (MIC) of ethanolic extract was performed by broth dilution method and the zone of inhibition was studied by agar disc diffusion method at concentrations of 2, 5 and 10mg/ml in DMSO. Ciprofloxacin (5µg/ml) and Cotrimazole (25µg/ml) were used as reference control for the antibacterial and antifungal studies respectively. The results of MIC study revealed the antimicrobial activity of the extract against the tested strains of microorganisms between concentration range of 50 and 400 µg/ml. The results of zone of inhibition study revealed concentration dependant nature of the extract with better effectiveness against gram-positive bacteria than gram-negative bacteria. The present study indicates the potential usefulness of Alternanthera sessilis Linn. aerial parts in the treatment of various pathogenic diseases as mentioned in the ayurvedic literature.